(untitled) (Scientific journal of the Fergana State University, 2023)
This article examines the problems of studying aesthetic assessment in the proverbial linguistic picture of the world. Aesthetic assessment is defined as an assessment based on certain subjectively determined aesthetic principles and a deep understanding of the aesthetic essence. A comprehensive study of aesthetic assessment in language is possible when studying the proverbial picture of the world, which is identified as a component of the linguistic picture of the world.